Hotel customer segmentation and sentiment analysis through online reviews: An analysis of selected European markets - Anderson S. Oliveira; Ana I. Renda; Marisol B. Correia; Nuno Antonio (Tourism & Management Studies)
This study aims to verify how distinct markets evaluate hotels in the Algarve through the analysis of online reviews, in order to identify if satisfaction and dissatisfaction attributes are similar among some of the main markets of overnight stay tourists in the region. Online reviews of hotels in the Algarve, written in English, French as well as Portuguese and posted on Tripadvisor by British, French and Portuguese residents from January 2019 to December 2019 are analysed. After the analysis of 8,596 online textual reviews, the results demonstrated that not only satisfaction and dissatisfaction rates towards hotel attributes differ according to the language, but also that customers from different countries place dissimilar emphasis on hotel attributes. Besides extending the current research on the use of online reviews, the findings of this study also assist hoteliers to identify improvement opportunities. Although many studies on marketing segmentation through data mining have been conducted, this paper analyses the customer satisfaction of relevant tourist markets and suggests up-to-date practical implications for hoteliers.